2017
DOI: 10.5888/pcd14.160406
|View full text |Cite
|
Sign up to set email alerts
|

Global Trends in the Affordability of Sugar-Sweetened Beverages, 1990–2016

Abstract: IntroductionThe objective of this study was to quantify changes in the affordability of sugar-sweetened beverages, a product implicated as a contributor to rising rates of obesity worldwide, as a function of product price and personal income.MethodsWe used international survey data in a retrospective analysis of 40 high-income and 42 low-income and middle-income countries from 1990 to 2016. Prices of sugar-sweetened beverages were from the Economist Intelligence Unit’s World Cost of Living Survey. Income and i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
44
0
3

Year Published

2017
2017
2022
2022

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 58 publications
(48 citation statements)
references
References 36 publications
1
44
0
3
Order By: Relevance
“…Another example of how consumer prices can influence oral health is given by the proportion of income needed to purchase sugar-sweetened beverages which has decreased worldwide since 1990 but particularly in LMIC. 139 Knai and colleagues have proposed a systems approach for analysing the commercial determinants of health. 140 Such an approach has the potential to promote a better understanding of the broader political, institutional, and cultural contexts in which health outcomes, risk factors and behaviours are embedded.…”
Section: Figure 3herementioning
confidence: 99%
“…Another example of how consumer prices can influence oral health is given by the proportion of income needed to purchase sugar-sweetened beverages which has decreased worldwide since 1990 but particularly in LMIC. 139 Knai and colleagues have proposed a systems approach for analysing the commercial determinants of health. 140 Such an approach has the potential to promote a better understanding of the broader political, institutional, and cultural contexts in which health outcomes, risk factors and behaviours are embedded.…”
Section: Figure 3herementioning
confidence: 99%
“…Limitations notwithstanding, this study is among the first to suggest that the impact of the tax on consumption may have been more modest than anticipated. Reasons for a modest impact may be the continued low price of SSB relative to healthier beverages (such as milk and 100% vegetable juice), high availability, aggressive marketing [9][10][11]42], as well as tax avoidance (purchasing SSB from retailers within Philadelphia who chose to not raise the price of SSB or purchasing from retailers outside of Philadelphia). Taken in context with other studies, it is important to conduct further research to understand the full effects of the tax on consumption, including research in larger population-based samples across multiple cities, as well as, among high-risk sub-populations.…”
Section: Discussionmentioning
confidence: 99%
“…High consumption of SSB is associated with increased risk of obesity, type 2 diabetes, cardiovascular disease and other health problems [3][4][5][6][7][8]. Reasons for high consumption include the low price of SSB relative to healthier beverages, high availability, and aggressive marketing [9][10][11]. A systematic literature review of food price elasticity found that the demand for SSB is responsive to price changes [12], which forms the basis for implementing a beverage tax to reduce consumption.…”
Section: Introductionmentioning
confidence: 99%
“…Due to the association between the consumption of soft drinks and various diseases and non-contagious demages, this consumption has been discouraged and several countries have adopted public health measures to maximize the reduction of consumption, and the increase in taxes on sugar-sweetened beverage, the most mentioned measure in the literature. [18][19][20][21][22] Data from sugarcane tax countries show that such a policy is effective in reducing the sale and consumption of soft drinks. In Mexico, after approval of this type of tax in 2013, there was a 12% decrease in per capita purchases of sugar-sweetened beverage after one year and 9.7% in the second year.…”
Section: Discussionmentioning
confidence: 99%